A luminescent bimetallic iridium(iii) complex for ratiometric tracking intracellular viscosity. Issue 11 (22nd January 2018) - Liu, Fengyu; Wen, Jia; Chen, Su-Shing; Sun, Shiguo
Abstract : The luminescent bimetallic iridium probeC10 could distinguish cancer cells from normal cells and track viscosity changes during cell apoptosis. Abstract : A luminescent bimetallic iridium probeC10 was developed through a long soft carbon chain linkage to achieve ratiometric detection of viscosity.C10 features high sensitivity and selectivity for viscosity. More importantly, C10 is living cell permeable and can be employed to distinguish cancer cells from normal cells and track viscosity changes during MCF-7 cell apoptosis.